1999
DOI: 10.1081/ada-100101866
|View full text |Cite
|
Sign up to set email alerts
|

Inhalant Abuse and the Abuse of Other Drugs*

Abstract: For children incarcerated in a juvenile detention facility in our community, inhalant abuse is associated with the later use of other substances of abuse. If this finding is replicated in other populations, it underscores the need for effective preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 14 publications
2
20
3
Order By: Relevance
“…First, it is associated with the use of multiple illicit drugs and injection drug use (Dinwiddie et al, 1991;Schutz et al, 1994). In particular, adolescents who were incarcerated in juvenile detention facilities appear to be at high risk of starting inhalant use early and using multiple drugs (McGarvey et al, 1996;Young et al, 1999). Bennett et al (2000) found that inhalant use before age 18 was associated with later use of hard drugs and binge drinking.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…First, it is associated with the use of multiple illicit drugs and injection drug use (Dinwiddie et al, 1991;Schutz et al, 1994). In particular, adolescents who were incarcerated in juvenile detention facilities appear to be at high risk of starting inhalant use early and using multiple drugs (McGarvey et al, 1996;Young et al, 1999). Bennett et al (2000) found that inhalant use before age 18 was associated with later use of hard drugs and binge drinking.…”
mentioning
confidence: 99%
“…Inhalants are often the first substance used by incarcerated youths (Young et al, 1999). Inhalant-using delinquents report greater antisocial attitudes, personal and familial dysfunction, peer deviance, suicidality, and substance abuse than their non-inhalant-using counterparts (Howard and Jenson, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of adolescents have found that inhalant use is frequently associated with delinquent or criminal activities (Howard and Jenson, 1999;Mackesy-Amiti and Fendrich, 1999;McGarvey et al, 1996;Wu et al, 2004;Young et al, 1999) and suggest that inhalant use may be more closely associated with delinquency than the use of other drugs (MackesyAmiti and Fendrich, 1999). In this adult sample, past year criminal activity was associated with inhalant use in our bivariate analyses only, and it was not common among past year inhalant users who had a inhalant use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, investigators have found a strong association between inhalant use, antisocial personality, and criminal behaviors, and they have considered inhalant use by minors as one of many delinquent behaviors (Compton et al, 1994;Howard and Jenson, 1999;McGarvey et al, 1996;MackesyAmiti and Fendrich, 1999;Young et al, 1999). For instance, youths who are incarcerated in juvenile detention facilities tend to initiate inhalant use early and to use multiple drugs (McGarvey et al, 1996;Young et al, 1999).…”
Section: Introductionmentioning
confidence: 99%